DETERMINANTS OF CLASSROOM SEATING ARRANGEMENT IN HIGHER EDUCATION INSTITUTIONS - G. SHAINY*, T. NEERAJA and V. PRASUNA, (The Journal of Research ANGRAU, 2020)
The study was to assess and evaluate the determinants of classroom seating arrangement in highereducation institutions in Guntur district of Andhra Pradesh. Thirty higher educational institutes (30 respondents)were selected for the study. Eleven design features that guide the seating arrangement in a classroom proposedby various higher educational institutes and official bodies served as a base for identifying the features toevaluate the seating arrangement in a classroom. The results showed that educational institutes were notpaying attention to the modified fan-shaped design configuration, theatre-style seating, and seating arrangementfor students with disabilities. The total strength of the students and year of establishment of the institutionwere the deciding factors in designing a seating arrangement in a class, row to row clearances, passageclearances, minimum and maximum distance between the last row to end wall, clearances from the student'sdesk adjacent wall, desk to desk clearances, seating for students with a disability and seating designconfiguration.